2011
DOI: 10.1016/j.neurobiolaging.2009.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin D deficiency improves mitochondrial function and learning/memory in aging Alzheimer disease mouse model

Abstract: Mitochondrial stress is one of the early features of Alzheimer disease (AD). Mitochondrial Aβ has been linked to mitochondrial toxicity. Our recent study demonstrated that cyclophilin D (CypD) mediated mitochondrial permeability transition pore (mPTP) is an important mechanism for neuronal and synaptic stress induced by both Aβ and oxidative stress. In transgenic AD-type mice overexpressing mutant amyloid precursor protein (APP) and Aβ (mAPP), CypD deficiency improves mitochondrial and synaptic function and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
229
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(237 citation statements)
references
References 39 publications
7
229
1
Order By: Relevance
“…[22] In transgenic mouse models for AD and in human AD sufferers, 17-HSD10 has been shown to have increased expression levels and has gained considerable attention as a result of its ability to bind A, suppress A-induced apoptosis and free-radical generation in neurons. [11] It is known that the interaction between 17-HSD10 and A , A and A (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) takes place in the nanomolar range (K d ~ 40-80 nM), [11] which agrees well with the low cellular concentrations of A peptide expected at the early stages of AD. In addition, mutagenesis and inhibition studies have suggested that the L D loop of 17-HSD10, comprising residues C91-D119, plays a critical role in A binding.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…[22] In transgenic mouse models for AD and in human AD sufferers, 17-HSD10 has been shown to have increased expression levels and has gained considerable attention as a result of its ability to bind A, suppress A-induced apoptosis and free-radical generation in neurons. [11] It is known that the interaction between 17-HSD10 and A , A and A (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) takes place in the nanomolar range (K d ~ 40-80 nM), [11] which agrees well with the low cellular concentrations of A peptide expected at the early stages of AD. In addition, mutagenesis and inhibition studies have suggested that the L D loop of 17-HSD10, comprising residues C91-D119, plays a critical role in A binding.…”
Section: Introductionsupporting
confidence: 72%
“…However, a lack of -sheet structure at acidic pH cannot exclusively account for the observed lack of aggregation inhibition, as it has been shown that 17-HSD10 does not bind A (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), which is known to exhibit a -sheet conformation by CD and NMR studies. [63] In contrast, the conformation of the N-terminal region, residues 17-20 of A (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) that constitute the binding interface with 17-HSD10, [11] is known to exhibit a random-coil/-helix/-sheet equilibrium that is highly dependent on pH conditions. [61,63,64] At pH 7-8, it has been demonstrated that residues 10-28, containing the putative 17-HSD10 binding interface, are in equilibrium between random coil and -helix conformations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CypD binds to the Aβ peptide, and Aβ peptide–CypD complexes were isolated from patients with Alzheimer's disease and transgenic mice (Du, Guo, Zhang, Rydzewska, & Yan, 2011; Du et al., 2008). These complexes potentiate mitochondrial, neuronal, and synaptic stress, and genetic deletion of CypD protects the brain from Aβ‐induced neuronal degeneration (Du et al., 2008, 2014; Guo et al., 2013).…”
Section: Evidence For the Involvement Of Mptp Opening In Age‐associatmentioning
confidence: 99%
“…These observations led us to consider a role of intracellular Aβ. Notably, recent studies have highlighted the role of mitochondrial Aβ in AD pathogenesis [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%